The Influence of Parental Attachment toward Early Childhood Children's Separation Anxiety - Astuti, Umi; Hartono, Hartono; Sunawan, Sunawan (Journal of Primary Education, 2020)
Most preschool children show incapabilities of overcoming anxieties so that they have negative emotions while parting with an intimate figure. This research examined parental attachment toward early childhood children's parting anxieties. The research population consisted of 793 participants aged 5-6 years old. The sampling technique was purposive sampling. It involved 185 early childhood children (87 boys and 98 girls). The data were collected through a questionnaire. The data technique used the Parental-Child Attachment-Child Survey questionnaire to measure parental attachment to children. Separation anxiety in early childhood was measured using the Children's Separation Anxiety Disorders (CSAS) questionaire. Each question item was read by the researcher to facilitate the children. The applied analysis was a simple linear regression. It was to analyze the parental attachment toward children's separation anxiety. The result shows Fcount = 15.26 < Ftable = 3.045 with a Sig value 0.000 < 0.05. It means high parental attachment lowered children's separation anxiety at schools. This child-parent intimacy supported adaptive social quality in a peer group. It also provided a positive foundation for their further development.